The Chinese sultanate Islam, ethnicity, and the Panthay Rebellion in southwest China, 1856-1873 - Atwill, David G. (Stanford University Press, 2005)
The first historical examination of a Muslim-led rebellion in mid-nineteenth-century China which carved out an independent sultanate along China's southwestern border lasting nearly seventeen years